KOMPETENSI PETANI JAGUNG DALAM BERUSAHATANI DI LAHAN GAMBUT (KASUS PETANI JAGUNG DI LAHAN GAMBUT DI DESA LIMBUNG KABUPATEN PONTIANAK KALIMANTAN BARAT) - Malta, Malta (Bumi Lestari, 2011)
Agricultural development is a series of efforts to increase farmers’ income, to create employment, to alleviate poverty, to assure food security, and to encourage regional economic development. By increasing agricultural products, it is hoped that farmers will be able to improve their income. In line with this effort, the quality of human resources in the field of agriculture is one of the essential factors in increasing agricultural products. The aims of this study were (1) to learn the competency level of corn farmers in peatlands, and (2) to identify the farmers characteristics related to the competency of corn farmers in peatlands. The research method used was descriptive-corelational. The research population consisted of 38 corn farmers in peatlands at Limbung village in Pontianak district, while the data collection was conducted on census basis from the 38 farmers. The data collection was carried out from August until September 2007. The analysis of the data was performed by using the correlation test of Rank Spearman. The research results showed that (1) the competency of corn farmers was of average level, (2) the competency was closely related to the age, formal education, and experience.
Keywords: corn farmer; competency; peatlands; farmers characteristics